2019
DOI: 10.1101/716456
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extracellular adenosine enhances the ability of PMNs to killStreptococcus pneumoniaeby inhibiting IL-10 production

Abstract: PMNs are crucial for initial control of Streptococcus pneumoniae (pneumococcus) lung infection; however, as the infection progresses their persistence in the lungs becomes detrimental. Here we explored why the anti-microbial efficacy of PMNs declines over the course of infection. We found that the progressive inability of PMNs to control infection correlated with phenotypic differences characterized by a decrease in CD73 expression, an enzyme required for production of extracellular adenosine (EAD). EAD produc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

6
0

Authors

Journals

citations
Cited by 11 publications
(55 citation statements)
references
References 72 publications
0
55
0
Order By: Relevance
“…We previously found that extracellular adenosine (EAD) production by PMNs is required for their antimicrobial activity against S . pneumoniae (Siwapornchai et al, 2020). To test if aging is associated with changes in the expression of EAD‐producing and degrading enzymes, we compared the basal expression of CD73, CD39, and ADA on the surface of bone marrow‐derived PMNs using flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously found that extracellular adenosine (EAD) production by PMNs is required for their antimicrobial activity against S . pneumoniae (Siwapornchai et al, 2020). To test if aging is associated with changes in the expression of EAD‐producing and degrading enzymes, we compared the basal expression of CD73, CD39, and ADA on the surface of bone marrow‐derived PMNs using flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…CD73 expression is crucial for the antimicrobial phenotype of PMNs during S pneumoniae infection (Siwapornchai et al, 2020). As pulmonary infection progresses, unresolved PMN presence in the lungs becomes detrimental for host resistance (Bou Ghanem, Clark, Roggensack, et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations